A practical model for building and enhancing trust in virtual teams - Cavicchioli, Matheus (Digital Repository of Theses - SSBM Geneva, 2023)
Studies confirm that information technology has been rapidly advancing in the last decades and, as an outcome, dramatically increasing the opportunities for companies to apply new tools for their own benefit (Liao, 2017). Morrison-Smith and Ruiz (2020) estimated that more than 85% of working professionals were engaged in some sort of virtual team, supporting the fact that this type of team is becoming vital to perpetuating our increasingly globalized environment. This is also supported by Krumm et al. (2016), who argue that the process of globalization involves collaborating to reduce the distance and increase the possibilities for companies and organizations to optimize their resources, especially human resources. This is possible through the introduction of new technology-mediated tools, which can create a wide range of possibilities for grouping people from different continents into the same virtual room. The concept of virtual teams topic is discussed widely in the literature (Backmann et al., 2020). Ford, Piccolo and Ford (2017), Laitinen and Valo (2018) and Lee, Park and Lee (2015) defined virtual teams as a skilled group of task-oriented individuals who are, to some extent, geographically dispersed and mostly working toward a common goal in a technology-mediated environment. In addition, organizations have shifted from team-based work to virtual teams in order to increase savings and flexibility, and this is predicted to keep evolving in the future (Laitinen and Valo, 2018).